Space Telescopes and Instrumentation 2020: Optical, Infrared, and Millimeter Wave 2020
DOI: 10.1117/12.2562656
|View full text |Cite
|
Sign up to set email alerts
|

Design of the life signature detection polarimeter LSDpol

Abstract: Many biologically produced chiral molecules such as amino acids and sugars show a preference for left or right handedness (homochirality). Light reflected by biological materials such as algae and leaves therefore exhibits a small amount of circular polarization that strongly depends on wavelength. Our Life Signature Detection polarimeter (LSDpol) is optimized to measure these signatures of life. LSDpol is a compact spectropolarimeter concept with no moving parts that instantaneously measures linear and circul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Raw linear-polarizer calibration images of LSDPol reveal a spurious signal in the zeroth diffraction order along the polarimetry dimension that was not expected by the Mueller model. 6 The liquid crystal spatial polarization modulator acts as a weak polarization grating. A diffraction that is created in the first optical element might explain why we see both the spurious signal in the zeroth order and the shifted V lookalike in the dispersed spectra.…”
Section: Numerical Simulation Including Fresnel Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw linear-polarizer calibration images of LSDPol reveal a spurious signal in the zeroth diffraction order along the polarimetry dimension that was not expected by the Mueller model. 6 The liquid crystal spatial polarization modulator acts as a weak polarization grating. A diffraction that is created in the first optical element might explain why we see both the spurious signal in the zeroth order and the shifted V lookalike in the dispersed spectra.…”
Section: Numerical Simulation Including Fresnel Diffractionmentioning
confidence: 99%
“…We can detect possible inhomogeneous illumination of the entrance slit by inspecting the projected 0th order. In the lab, Keller et al (2020) 6 found that this slit image is modulated even in the case of incoming unpolarized light and that the spectra of contain a spurious modulation with a frequency equal to a V modulation, but phase-shifted by 90 degrees as compared to the modulation for incoming circularly polarized light. These will be referred to as the spurious signal and the shifted V lookalike, respectively.…”
Section: Introductionmentioning
confidence: 99%